Anthropometric characteristics, physical fitness and technical performance of under-19 soccer players by competitive level and field position - Rebelo, A.; Brito, J.; Maia, J.; Coelho e Silva, M. J.; Figueiredo, A. J.; Bangsbo, J.; Malina, R. M.; Seabra, A. (International Journal of Sports Medicine, 2013)
Anthropometric characteristics, physical fitness and technical skills of under-19 (U19) soccer players were compared by competitive level (elite, n=95; non-elite, n=85) and playing position (goalkeeper, central defender, fullback, midfield, forward). Fitness tests included 5- and 30-m sprints, agility, squat jump (SJ) and countermovement jump (CMJ), strength and Yo-Yo intermittent endurance test level 2 (Yo-Yo IE2). Soccer-specific skills included ball control and dribbling. Independent of position, elite players presented more hours of training per year than non-elite players (d>1.2). Stature and body mass discriminated elite from non-elite players among goalkeepers and central defenders (d>0.6). Major differences were noted between elite and non-elite goalkeepers for SJ, CMJ, Yo-Yo IE2, and ball control (d>1.2). Elite central defenders performed better than their non-elite counterparts in SJ and ball control tests (d>1.2). Elite players presented better agility and Yo-Yo IE2 performances than non-elite players within all positional roles (d>0.6). In conclusion, U19 players differed in anthropometric characteristics, physical fitness and technical skills by competitive level within field positions.